Stoichiometry and structure of complexes of DNA oligomers with microgonotropens and distamycin by 1H NMR spectroscopy and molecular modeling. - Blaskó, A (1993)
Dien-microgonotropen-c (5c), tren-microgonotropen-b (6b), and distamycin (Dm) bind the A.T-rich region of d(CGCAAATTTGCG)2 (oligo-12) and form 1:1 (5c and 6b) and 2:1 and 4:1 (Dm) complexes. At 1.75 mol ratio of Dm/oligo-12 the 4:1 complex starts to form and coexists with the 2:1 complex and the free double-stranded DNA. No 1:1 and 3:1 complexes were seen, implying a preferential dimeric binding mode of Dm to oligo-12. At 4:1 mol ratio of Dm/oligo-12 there is extensive exchange of the A.T imino protons with the solvent at the binding site. This is presumably due to the opening of the minor groove. Molecular modeling shows that four Dm molecules can fit in a tandem antiparallel way into the minor groove of oligo-12 by widening it to 16-17 A. On going from oligo-12 to the pseudosymmetrical hexadecamer oligo-16 [d(GGCGCAAATTTGGCGG).d(CCGCCAAATTTGCGCC)] the stoichiometry of binding of 5c changes from 1:1 to 2:1. Since oligo-12 and oligo-16 have the same A.T binding site this change in stoichiometry is due to the increase in the G.C terminal pairing. Hoechst 33258 displaces the two 5c molecules bound in the minor groove of oligo-16 at the A.T region. Marked exchange of A.T imino protons was seen in the case of (oligo-16).(Ht)2.